CORRELATION BETWEEN THE STUDENTS VOCABULARY MASTERY AND THEIR ABILITY IN TRANSLATING ENGLISH TEXT INTO INDONESIAN AT MAS AL-BAROKAH KOLESE - Nadia Nadia; Juamdan Zamha Zamihu; Baharudin Adu (English Education Department, 2022)
The formulation of the problem in this study is whether there is a correlation between students' vocabulary mastery and their ability to translate English texts into Indonesian at MAS Al-Barokah Kolese students. The purpose of this study was to determine whether there was a correlation between students' vocabulary mastery and their ability to translate English texts into Indonesian at MAS Al-Barokah Kolese students. Data collection in this study was carried out using a research instrument in the form of a test to students to determine the correlation between students' vocabulary mastery and their ability to translate English text into Indonesian. This research is a quantitative research. The subjects of this study were 27 grade 10 students of MAS Al-Barokah Kolese. Data were analyzed using Statistical Product and Service Solution (SPSS) version 22.0. Based on the results of research and data analysis, it was concluded that there was a correlation between students' vocabulary mastery and their ability to translate English texts into Indonesian from grade 10 students at MAS Al-Barokah Kolese. This conclusion is based on the results of statistical analysis which found a significance level of 0.996 with an r table value of 0.381. The rxy value is greater than the r table value (0.996> 0.381) and the significance value is less than (0.5) or in other words the Null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted.